29x+29=28x-11

Simple and best practice solution for 29x+29=28x-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 29x+29=28x-11 equation:



29x+29=28x-11
We move all terms to the left:
29x+29-(28x-11)=0
We get rid of parentheses
29x-28x+11+29=0
We add all the numbers together, and all the variables
x+40=0
We move all terms containing x to the left, all other terms to the right
x=-40

You can always share this solution

See similar equations:

| -2-6x-8=-8x+24 | | 3x-61=-50 | | 8(6x-4)=208 | | 9x+154=199 | | 7088=2*3.13*9.5^2+2*3.14*9.5*x | | 45.5=5n | | n10+9=17 | | -11+m=4 | | 3x+7-2x+5=x+2 | | 4y-5+3y=3” | | -14+5y=46 | | X+1/12-3x+7/4=7 | | 8x+17=129 | | 8x+4=4x8 | | 6x+10+2x-12=42 | | 1.9?7.1x=1.9 | | 6y+63=13y | | x²-50x+400=0 | | 0.4k+3.9=5.78 | | -8x+3=83 | | 12-b=12/5 | | 4*(x-7)=0.3*(x+2)+2.11 | | b+0.2=2.5-7 | | 4p–13=3 | | 475000(1.0375)^t=1,000,000 | | 3m÷10=6 | | r12=-9 | | 4x^2-56x+20=0 | | 15+12+x=90 |

Equations solver categories